Um estudo sobre alterações ambientais independentes da reposta: desamparo aprendido, comportamento supersticioso e o papel do relato verbal - Perroni, Carolina Escalona (2006)
The present study investigated the effects of exposure to aversive events- controllable and incontrollable on the performance of young adults on an escape/avoidance task that followed such exposure. A second goal of the present study was to evaluate the possible effects of requests of verbal reports over the participants performances. Participants were 40 adults assigned to 3 groups: participants of the Escape Group were exposed to a Training Condition when an aversive sound could be turned off by his/hers responses. These participants were, then, exposed to a Test Condition (40 trials) where a second response turned off the same sound. Participants of the Yoked Group where exposed to a Training Condition similar to the Escape Group, but no responses were effective to turn off the sound. The same Test condition was programmed for participants off the Yoked and Control Groups. Participants off the Escape and Yoked Groups were assigned to 1 of 3 conditions of verbal report: they were asked if they know how to turn off the sound on the 40th trial, or 3 different trials, or on 23 trials of the Training Condition. Results did not suggest the common effects associated with helplessness. Results also showed that the verbal reports did not contribute to the emergence or to the prevention of helplessness. Results showed, on the other hand, that certain patterns of responding on the Training Condition were closely related to participants performances on the Test Condition